2000
DOI: 10.2337/diacare.23.4.472
|View full text |Cite
|
Sign up to set email alerts
|

The association of diabetes specialist care with health care practices and glycemic control in patients with type 1 diabetes: a cross-sectional analysis from the Pittsburgh epidemiology of diabetes complications study.

Abstract: R E S U LT S -Patients who re p o rted receiving specialist care were more likely to be female, to have an education level beyond high school, to have an annual household income $ 2 0 , 0 0 0 , and to have health insurance. Additionally, patients receiving specialist care were more likely to have received diabetes education during the previous 3 years, to have knowledge of HbA 1 c t e s ting and to have received that test during the previous 6 months, to have knowledge of the Diabetes Control and Complications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
1
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 0 publications
4
56
1
1
Order By: Relevance
“…Despite a large proportion of subjects having regular health care (at least one visit per year), control remained suboptimal throughout (5), which may represent a breakdown in communication between provider and patient. Previous studies assessing type of health care provider accessed by EDC participants indicated that at exam 6, ϳ50% of the cohort reported receiving care from a diabetes specialist (13,28); thus, it is unlikely that type of provider played a significant role in the results.…”
Section: Correlates Of Awareness and Treatmentmentioning
confidence: 84%
See 1 more Smart Citation
“…Despite a large proportion of subjects having regular health care (at least one visit per year), control remained suboptimal throughout (5), which may represent a breakdown in communication between provider and patient. Previous studies assessing type of health care provider accessed by EDC participants indicated that at exam 6, ϳ50% of the cohort reported receiving care from a diabetes specialist (13,28); thus, it is unlikely that type of provider played a significant role in the results.…”
Section: Correlates Of Awareness and Treatmentmentioning
confidence: 84%
“…dren's Hospital was one of the eligibility criteria, the EDC participants subsequently received their diabetes care in the general community, with ϳ50% receiving care from diabetes specialists (13). The present cross-sectional analyses represent data available for adults (age Ͼ18 years) followed for the first 10 years (six examination periods) of the EDC.…”
Section: Research Design and Methods -mentioning
confidence: 99%
“…Patient acceptance of basal/bolus insulin regimens has been slow (6,7), perhaps because of the considerable burden of multiple injections for some (8,9). Inhaled insulin may provide an alternative for the management of type 1 diabetes as part of a basal/bolus strategy in patients who are unwilling or unable to use preprandial insulin injections.…”
mentioning
confidence: 99%
“…Specifically, specialist care visits have been linked to improvements in blood pressure management, foot ulcers, infection, and screening for complications. These data provide additional evidence of the utility of specialty care visits (17)(18)(19). Along with intensive therapy and specialist care visits, visiting a physician at least two times per year was also positively associated with each screening test evaluated.…”
Section: Screening Frequency and Characteristicsmentioning
confidence: 83%